Analisis Tingkat Kemampuan Berpikir Kritis Dengan Model Perubahan Konseptual Ditinjau Dari Gaya Belajar Siswa - Dedi Riyan Rizaldi; Muh. Makhrus; Aris Doyan (Department of Physics Education, Universitas Mataram, 2019)
This study aims to determine level of critical thinking ability when learning process kinetic theory of gas with conceptual change model outcome review from high school student learning style. This type of research is pre experiment with factorial design ÃÂ (level 3). The research population is all grade XI IPA in SMA Negeri 7 Mataram with sampling technique using purposive sampling. Three samples were taken as experimental class which is class XI MIPA 1 taught with CCM visual style, XI IPA 2 taught by CCM auditory style, and XI IPA 3 taught with CCM kinesthetic style. The student learning style data on was taken using by questionnaire with 4 alternative options. The critical thinking abilityÃ¢â¬â¢s data collected by using sheets of critical thinking skill based on student's answer to LKS. The result data was analyzed with descriptive statistical test and classified based on categorization level of critical thinking ability. Based on the analysis result, it can be concluded level of critical thinking ability when learning process kinetic theory of gas with conceptual change model outcome review from high school student learning style including into medium category with value of 70,87.